Characterization and Nitrogen Fixation Efficiency of Rhizobia Isolated from Albizia Lebbek Benth - Kaur, Ajeet (Indian Forester, 2015)
Thirteen rhizobial isolates were obtained from the root nodules of Albizia lebbek seedlings from different places and tested for nodulation, growth on different combinations of carbon and nitrogen sources, tolerance against heavy metals, salt and antibiotics. Five rhizobial isolates were selected to study nitrogen fixation potentional in A. lebbek seedlings during the active growth period (June to November) under glass house conditions. Both the isolates from Kiratpur Sahib (Punjab) viz., V(1) and V(2) were found highly resistant to heavy metals as well as salt. The mean generation time estimated for the isolate VI(1) was 3.38 h. Second order polynomial regression equations established between A620 and cell count for the isolates II(2) and VI(1) showed high coefficient of determination. The maximum 620 nodular dry weight (0.782 g) was recorded in seedlings inoculated with isolate IV(1) followed by III(2) in September. Seedlings inoculated with isolate III(2) from Lalpani maintained overall high nitrogenase activity throughout the active growth period.